Knowledge among patients with Hepatitis C initiating on direct-acting antiviral treatment in rural Rwanda: A prospective cohort study - Dale A Barnhart; Innocent Kamali; Francoise Nyirahabihirwe; Carol Mugabo; Jean de la Paix Gakuru; Mariam Uwase; Esdras Nizeyumuremyi; Tumusime Musafiri; Jean de Dieu Gatete; Jean Damascene Makuza; Fredrick Kateera; Bethany Hedt-Gauthier; et al. (Taylor & Francis Group, 2021)
Background Curative direct-acting antiviral treatment (DAA) has made it plausible to implement hepatitis C elimination interventions. However, poor hepatitis C knowledge among patients could impede the effectiveness of screening and treatment programs. Objective We assessed knowledge on hepatitis C among rural Rwandans initiating DAA treatment for hepatitis C in a prospective cohort. Methods We administered 15 true-false statements before treatment initiation and during one follow-up visit occurring either 1 or 2 months after treatment initiation. We assessed the average number of correct responses per patient, the proportion of correct responses to individual statements, pre-treatment predictors of knowledge, and whether post-initiation knowledge was associated with time since treatment initiation, quality of care, or adherence. Results Among 333 patients who answered knowledge questions before treatment initiation, 325 (97.6%) were re-assessed at a post-initiation visit. Pre-initiation, 72.1% knew hepatitis C was curable, 61.9% knew that hepatitis C could cause liver damage or cancer, and 42.3% knew that people with hepatitis C could look and feel fine. The average number of correct responses was 8.1 out of 15 (95% CI: 7.8-8.5), but was significantly lower among those with low educational attainment or with low literacy. Post-initiation, correct responses increased by an average of 2.0 statements (95% CI: 1.6, 2.4, p-value <0.001). Many patients still mistakenly believed that hepatitis C could be transmitted through kissing (66.5%), eating utensils (44.1%), handshakes (34.8%), and hugs (34.8%). Post-initiation knowledge is inversely associated with self-reported quality of care and unassociated with self-reported adherence. Conclusion Although knowledge improved over time, key gaps persisted among patients. Accessible public education campaigns targeted to low-literacy populations emphasizing that hepatitis C can be asymptomatic, has severe consequences, and is curable could promote participation in mass screening campaigns and linkage to care. Visual tools could facilitate clinician-provided patient education.